Nano- and submicrocrystalline steels processed by severe plastic deformation - Dobatkin, S.V. (Физика и техника высоких давлений, 2008)
The aim of this paper is to consider the features of structure evolution during severe plastic deformation (SPD) of steels and its influence on mechanical properties. The investigations have been carried out mainly on low-carbon steels as well as on austenitic stainless steels after SPD by torsion under high pressure (HPT) and equal-channel angular pressing (ECAP). Structure formation dependences on temperature deformation conditions, strain degree, chemical composition, initial state and pressure are considered. The role of phase transformations for additional grain refinement, namely, martensitic transformation, precipitation of carbide particles during SPD and heating is underlined.